Integrating AI in Project-Based Learning for Differentiated English Language Instruction: A Scoping Review - Arqam; Andi Asrifan (Journal of English Education and Teaching)
This scoping study examines the integration of Artificial Intelligence (AI) in Project-Based Learning (PBL) for diversified English language training and its benefits, drawbacks, and trends. Arksey and O'Malley's approach and PRISMA-ScR systematically review peer-reviewed articles from the last decade from Google Scholar, Scopus, ERIC, DOAJ, PubMed, and Science Direct. A complete literature search, inclusion-based selection, data extraction, and thematic analysis are used. AI can improve PBL by offering individualized learning, real-time feedback, and immersive learning settings. Intelligent virtual assistants, smart grading systems, and adaptive learning technologies provide personalized instruction that improves learning results and inclusivity. However, the analysis also notes ethical issues connected to data privacy and algorithmic biases and the need for teacher training to use AI in schools effectively. Despite these obstacles, AI in PBL can transform English language instruction by encouraging critical thinking, cooperation, and communication. This scoping review concludes that AI in PBL can transform differentiated English language instruction. To fully realize the benefits of AI-integrated PBL and improve English language learning for all students, research and innovation must continue.